Field evidence suggests that the Palaeoproterozoic Gowganda Formation in Canada is non-glacial in origin - Molén, Mats O. (Geologos, 2021)
During more than a century since its original identification, the Gowganda Formation in Ontario (Canada) has gradually been reinterpreted from representing mainly subglacial tillites to secondary gravity flow and glaciomarine deposits. The main pieces of geological evidence advanced in favour of glaciation in recent articles are outsized clasts that have been interpreted as dropstones and patches of diamictites in a single small-sized area at Cobalt which is still interpreted as displaying subglacial basal tillites. The present research considers field evidence in the Gowganda Formation in the light of more recent work on gravity flows linked to tectonics. Detailed studies have demonstrated that the clasts which are interpreted to be dropstones rarely penetrate laminae and are commonly draped by sediments the appearance of which is similar to lonestones in gravity flows. The “subglacial area” at Cobalt displays evidence of tectonics and gravity flows, which can be traced from the underlying bedrock, and then further in the overlying sequence of diamictites and rhythmites. The sum of geological features displays appearances at odds with a primary glaciogenic origin, and there is no unequivocal evidence present of glaciation. The data indicate deposition by non-glaciogenic gravity flows, including cohesive debris flows for the more compact units, probably triggered by tectonic displacements.